(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2010)
Objectives: To determine status of the adolescents in the context of education, nutrition, gender role, employment and reproductive rights in selected member countries of SAFOG. Materials and methods: An analysis has been made through review of printed and electronic resources on selected parameters of adolescent health. Results: The opportunity of primary education is not universal and gross disparity in youth literacy rate between male and female exist in most countries except a few. Malnutrition is quite prevalent in some countries reflected by a high proportion of low birth weight newborn and stunted adolescents. Employment opportunities for adolescent girls are less than the boys and many are engaged in non productive and domestic work. Gender discrimination is quite pronounced in how girls and boys are socialized, in household food allocation, opportunity for education, employment and in wage for work. In the traditional culture of this region talking about sex is a taboo and adolescents are poorly informed with regard to their own sexuality, physical well being, health and rights. Conclusion: The sheer number of adolescents and their great potential of physical, mental and social development have made them a special group to be dealt with priority. Professional bodies like SAFOG can take a leading role in this respect. DOI: 10.3329/bjog.v24i1.6323 Bangladesh J Obstet Gynaecol, 2009; Vol. 24(1) : 22-26